Structured Method to Establish the Enhance of Fatigue Life of Mechanical System Such as a Drawer by Accelerated Tests - Woo, Seongwoo; O’Neal, Dennis L.; Hassen , Yimer Mohammed; Mebrahtu, Gezae (Recent Progress in Science and Technology Vol. 7, 2023)
Parametric Accelerated Life Testing (ALT) is suggested as a method to locate design flaws and lessen fatigue failure in order to increase the lifespan of a mechanical system. It also includes a sample size equation for the ALT and a derivation of the generalized time to failure model by the linear transport process. As an example, a refrigerator drawer was given. The center support was bent and the rail rollers broke after loading. The rail roller support was lengthened, and the center support received additional ribs. The box cover at the first ALT failed close to where the cover and body converged. The rib and fillet were then added in greater amounts to the box. The center support and rails fractured at the second ALT. They were changed by thickening the rib and rounding the corners. There were no problems after the third ALT. The drawer life was guaranteed to be B1 life 10 years.